Canonical germinant receptor is dispensable for spore germination in Clostridium botulinum group II strain NCTC 11219 - Charlien Clauwers; Cédric Lood; Bram Van den Bergh; Vera van Noort; Chris W. Michiels (Scientific Reports, 2017)
Abstract Clostridium botulinum is an anaerobic sporeforming bacterium that is notorious for producing a potent neurotoxin. Spores of C. botulinum can survive mild food processing treatments and subsequently germinate, multiply, produce toxin and cause botulism. Control of spore germination and outgrowth is therefore essential for the safety of mildly processed foods. However, little is known about the process of spore germination in group II C. botulinum (gIICb), which are a major concern in chilled foods because they are psychrotrophic. The classical model of spore germination states that germination is triggered by the binding of a germinant molecule to a cognate germinant receptor. Remarkably, unlike many other sporeformers, gIICb has only one predicted canonical germinant receptor although it responds to multiple germinants. Therefore, we deleted the gerBAC locus that encodes this germinant receptor to determine its role in germination. Surprisingly, the deletion did not affect germination by any of the nutrient germinants, nor by the non-nutrient dodecylamine. We conclude that one or more other, so far unidentified, germinant receptors must be responsible for nutrient induced germination in gIICb. Furthermore, the gerBAC locus was strongly conserved with intact open reading frames in 159 gIICb genomes, suggesting that it has nevertheless an important function.